IMPLEMENTASI SERTIFIKASI HALAL PADA PRODUK PANGAN DI KOTA BENGKULU - Nukeriana, Debbi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
Halal certification is a process to obtain  halal certificate in accordance with Islamic Shari’ah it, aims to provide  legal certainty  of the halalness  of a product  so that it can reassure  the heart  for those  who consume it. This study is motivated by the number of food producers in Bengkulu City who do not do halal certification. This research  raised the problem  about  the implementation of halal certification, supporting and inhibiting factors and the role of LPPOM MUI of Bengkulu Province in im- plementing halal certification on food products  in Bengkulu City. The purpose of this research  is to analyze the implementation of halal certification, identify the supporting and inhibiting factors and to explore and find the role of LPPOM MUI of Bengkulu Province  in implementing halal certification on food products  in Bengkulu  City. This type of research  is a field research  using a sociological juridical approach that examines the applicable  legal provisions  and  what happens on the ground. In collecting the data the research  used interviews and document studies. The technique of data analysis is descriptive qualitative  by way of interpretation, triangulation and content  analysis. From the research  result, it can be concluded that first, the implementation of halal certification on food products  in Bengkulu City has been  implemented although still a small part of the number of Small and  Medium Industry (IKM) in Bengkulu  City. Secondly,  the supporting factor for the implementation of halal certification in food products  in Bengkulu City is to provide  a sense of comfort and  confidence in a product,  consumers of majority food are Muslim and increase  income / turnover  of food producers. As for the inhibiting factors are the Law on Halal Product  Guarantee is still voluntary  (voluntary),  lack of information / knowledge  about  halal certification and  constrained halal certification cost. Third, the Role of LPPOM MUI of Bengkulu Province in the implementation of halal certification on food products  in Bengkulu City is to protect the public against illicit products.  It also provides socialization of halal certification either through  formal means such as training and socialization or unofficially such as to family, friends and friends